Behavioural intervention to increase physical activity in adults with coronary heart disease in Jordan - Alsaleh, Eman; Windle, Richard; Blake, Holly (BioMed Central, 2016)
Background: Patients with coronary heart disease often do not follow prescribed physical activity recommendations. The aim of this study was to assess the efficacy of a behavioural intervention to increase physical activity in patients with coronary heart disease not attending structured cardiac rehabilitation programmes. Methods: Parallel randomised controlled trial comparing 6-month multi-component behavioural change intervention (n = 71) with usual care (n = 85) was conducted in two hospitals in Jordan, Middle East. Intervention included one face-to-face individualised consultation, 6 telephone support calls (for goal-setting, feedback and self monitoring) and 18 reminder text messages. Patients were randomly allocated to the two groups by opening opaque sealed sequence envelopes. The patients and the researcher who provided the intervention and assessed the outcomes were not blinded. Outcomes were assessed at baseline and 6 months. Primary outcome was physical activity level, secondary outcomes were blood pressure, body mass index, exercise self-efficacy for exercise and health-related quality of life. Results: Intervention and control groups were comparable at baseline. Moderate physical activity significantly increased in the intervention group compared with control group (mean change (SD) of frequency: 0.23 (0.87) days/week versus -.06 (0.40); duration: 15.53 (90.15) minutes/week versus −3.67 (22.60) minutes/week; intensity: 31.05 (105.98) Metabolic equivalents (METs) versus 14.68 (90.40) METs). Effect size was 0.03 for moderate PA frequency, 0.02 for moderate PA duration and 0.01 for moderate PA intensity. Walking significantly increased in the intervention group compared with control group (mean change (SD) of frequency: 3.15 (2.75) days/week versus 0.37 (1.83) days/week; duration: 150.90 (124.47) minutes/week versus 24.05 (195.93) minutes/week; intensity: 495. 12 (413.74) METs versus 14.62 (265.06) METs). Effect size was 0.36 for walking frequency, 0.05 for walking duration, 0.32 for walking intensity and 0.29 for total PA intensity. Intervention participants had significantly lower blood pressure, lower body mass index, greater exercise self-efficacy and better health related quality of life at 6 months compared with controls. Conclusions: Multi-component behavioural intervention increases physical activity, and improves body composition, physiological and psychological outcomes in CHD patients not attending structured rehabilitation programmes. Trial registration: Current Controlled Trials retrospectively registered in 21-03-2012. ISRCTN48570595